The Peripheral Vascular Status in Individuals with Type 2 Diabetes Mellitus - Imroatul Farida; Nur Muji Astuti; Yudha Bayu Firmansyah; Didik Dwi Winarno (Jurnal Ilmiah Kesehatan, 2022)
Poor vascularization in individuals with diabetes will worsen blood circulation due to high glucose in the blood. One of the risk factors leading to diabetic foot ulcers (DFU) is peripheral vascular disease. This study aims to identify the peripheral vascular status in individuals with type 2 diabetes mellitus (T2DM) at Kebonsari Public Health Centre, Surabaya. The research design in this study used a quantitative descriptive approach. There were 40 respondents with an accidental sampling. The data collection was carried out for four weeks, from May to June 2020. The research instrument was an observation sheet to record the Dorsalis Pedis artery pulse and ankle-brachial index (ABI). In addition, a digital sphygmomanometer was used to measure the Dorsalis Pedis artery pulse. Most respondents had the normal Dorsalis Pedis artery pulse in the right legs (80%), 20% had bradycardia, and none had tachycardia (0%). In addition, they had the normal Dorsalis Pedis artery pulse in the left legs (70%), 20% had bradycardia, and none had tachycardia (0%). Furthermore, they had the normal ABI values in the right legs (55%), 45% had borderline ABI values, and none had ischemic and critical ischemic (0%). In addition, they had the normal ABI values in the right legs (52%), 47% had borderline ABI values, and none had ischemic and critical ischemic (0%). Most individuals with T2DM at the Kebonsari Public Health Center, Surabaya, had normal peripheral vascular status. However, few respondents had bradycardia in the Dorsalis Pedis artery pulses, and almost half had borderline ABI values.